Design as Design. - Thompson, Christopher (S.l. : s.n., 1997)
Burnaz, Myriam ; Demeulemeester, Ann ; Heyndrickx, Tony ; Venlet, Danny ; Van Severen, Maarten ; Traces de Doigts
Design as Design, At Encore, Brussels ; Stijl, Brussels, April 26 until July 19, 1997
boek